Penerapan Model Pembelajaran Artikulasi Untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Kelas IV SD GMIM 1 Kakaskasen - Mersty E. Rindengan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to improve student learning outcomes in learning Indonesian in reading stories through the application of articulation learning models to fourth grade students at SD GMIM 1 Kakaskasen. The design model used is a class action research design (PTK) which consists of four stages: (1) planning stage (2) action stage (3) observation stage (4) reflection stage, which is carried out in two cycles. Data was collected by observing and testing. Data analysis techniques were carried out on learning outcomes that had been completed using the formula KB = T/Tt x 100%. The results showed that the learning outcomes of the first cycle were 64.37%, while the results of the second cycle were 85.62%. In this case, there was an increase in the learning outcomes of Indonesian language students in class IV SD GMIM 1 Kakaskasen by using the articulation learning model. Based on the results of the study, it can be concluded that the application of the articulation learning model can improve Indonesian language learning outcomes in folklore material for fourth grade students at SD GMIM 1 Kakaskasen. So it is suggested to teachers in teaching, Indonesian language subjects especially in class IV SD GMIM 1 Kakaskasen can apply an articulation learning model so that learning outcomes can run optimally.